The redistributive effects of monetary policy - Olivier Ledoit (University of Zurich, Department of Economics, 2011)
We introduce a model of the economy as a social network. Two agents are linked to the extent that they transact with each other. This generates well-defined topological notions of location, neighborhood and closeness. We investigate the implications of our model for monetary economics. When a central bank increases the money supply, it must inject the money somewhere in the economy. We demonstrate that the agent closest to the location where money is injected is better off, and the one furthest is worse off. This redistribution channel is independent from the ones previously noted in the literature. Symmetrically, any decrease in the money supply redistributes purchasing power in the other direction. We also outline the testable implications of our model.
Keywords: E40; E50; 330; money; redistribution; policy; central bank; social network; topology; Geldpolitik; Verteilungswirkung; Geldmenge; Kaufkraft; Tauschwirtschaft; Agentenbasierte Modellierung; Theorie